The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1016/j.juro.2010.06.113
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Tibial Nerve Stimulation Effects on Detrusor Overactivity Incontinence are Not Due to a Placebo Effect: A Randomized, Double-Blind, Placebo Controlled Trial

Abstract: Percutaneous tibial nerve stimulation can be considered an effective treatment for detrusor overactivity incontinence with 71% of patients considered responders, while none of those treated with placebo was considered a responder. The relevance of a placebo effect seems to be negligible in this patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
139
1
12

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(154 citation statements)
references
References 14 publications
2
139
1
12
Order By: Relevance
“…Urge incontinence episodes per day decreased from 3/day at baseline to 0.3/day at 12 weeks vs. 1.8/ day at baseline to 1.0/day for sham (p<0.001). [19] In a randomized, controlled study, Finazzi-Agro et al [17] reported that PTNS significantly increased voided volume than sham treatment (150-186 mL in the PTNS treatment group vs. 146-150 mL in the sham group, p<0.001). In a urodynamic study, Klingler et al [21] reported that PTNS increased the mean total bladder capacity from 197 mL at baseline (range 35-349 mL) to 252 mL (range 78-384 mL, p<0.01) after 12 weeks of therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Urge incontinence episodes per day decreased from 3/day at baseline to 0.3/day at 12 weeks vs. 1.8/ day at baseline to 1.0/day for sham (p<0.001). [19] In a randomized, controlled study, Finazzi-Agro et al [17] reported that PTNS significantly increased voided volume than sham treatment (150-186 mL in the PTNS treatment group vs. 146-150 mL in the sham group, p<0.001). In a urodynamic study, Klingler et al [21] reported that PTNS increased the mean total bladder capacity from 197 mL at baseline (range 35-349 mL) to 252 mL (range 78-384 mL, p<0.01) after 12 weeks of therapy.…”
Section: Discussionmentioning
confidence: 99%
“…[13] More than 30 studies regarding PTNS have been published. The earliest ones are case series or single-arm efficacy studies, [14][15][16] three are randomized, controlled trials, [9,17,18] and two are long-term follow-up studies of patients who were responders in the overactive bladder innovative therapy (OrBIT) and sham effectiveness in the treatment of overactive bladder symptoms (SUmiT) trials. [19,20] Over half of the patients receiving PTNS therapy in the SUmiT trial, a randomized, double-blinded, sham controlled study, reported moderate or marked improvement in bladder symptoms (54.5% in PTNS patients vs. 20.9% in sham, p<0.001).…”
Section: Discussionmentioning
confidence: 99%
“…When compared to sham procedure, the number or percentage of responders in PTNS group were statistically higher (p<0.01), not only in objective responses [32][33][34] but also in global response assessment (GRA) improvement or cure. 35 The significant reduction of symptoms in PTNS group compared to sham group were found in frequency, urinary incontinence, and nocturia episodes.…”
Section: Efficacymentioning
confidence: 99%
“…35 The significant reduction of symptoms in PTNS group compared to sham group were found in frequency, urinary incontinence, and nocturia episodes. 32,33,35 In the matter of voided volume, two studies comparing PTNS and sham procedure by Agro et al 33 In studies comparing PTNS and anti-muscarinic, there were variable results in changes of voiding diaries symptoms. Most of them showed significant reduction of symptoms in both groups with no significant difference.…”
Section: Efficacymentioning
confidence: 99%
“…Vandoninck et al [26] evaluated 90 patients with colleagues [35] performed a study on cat's bladder and found that intravenous inhibition of the metabotropic glutamate receptors and opioid receptors reduced PTNS efficacy in bladder overactivity. The posterior tibial nerve stimulation effect on supraspinal centers has been verified in humans in a study published by Finazzi Agro and colleagues [36] in which they found a significant increase in amplitude of long latency somatosensory evoked potentials recorded 24 hours after termination of a 12 sessions PTNS.…”
Section: Discussionmentioning
confidence: 99%